My research journey: why do i choose the qualitative methodology over the quantitative one?/ Saidatul Akmar Ismail - Ismail, Saidatul Akmar (Fakulti of Information Management, Universiti Teknologi MARA, 2015)
The research employs qualitative research jot: the project, focusing on factors, and using a qualitative method, within an interpretive philosophy. Interpretivism is a suitable epistemology for framing a study about process, which is widely agreed to be a complex, subjective, and abstract phenomenon that does not exist independently from people's activities. Interpretive research is valuable for its ability to produce deep insights into IS phenomena. Therefore, in this paper, a paradigm of a research and an interpretive philosophy are discussed in order to understand how both concepts could produce deep insights into the research problem of the study which is poorly understood: the way in which IL is implemented in the primary schools.